2014
DOI: 10.1039/c3nr06183c
|View full text |Cite
|
Sign up to set email alerts
|

The role of metal layers in the formation of metal–silicon hybrid nanoneedle arrays

Abstract: We investigated nanoneedle arrays fabricated on a series of metal-silicon substrates using Ga(+) ion beam patterning. It is shown that the low sputtering rate of the metal is preserved on the tip of each nanoneedle in the form of a gallium alloy nanodot. The generated nanodot was found to greatly alleviate the ion sputtering of the underlying materials. These protective metals are promising materials that act as a shelter for the functional layer, which is vulnerable to ion beam irradiation. In the present wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The electrochemical degradation of R-6G relies on the mass and charge transfer; therefore, the surface area-to-volume (SA/V) ratio of the electrode material and the presence of active sites play a crucial role in the entire process. It is reported that array structures could provide a significant enhancement in many fields of study, such as catalysis [19][20][21][22][23], anti-reflection coatings [24,25], solar cells [26,27], optoelectronics [28], surface property modifications [29], and biomedical applications [30]. Recent research works demonstrated that improvement could originate from an increased SA/V ratio and surface energy content of the samples, the presence of active sites and defects, as well as the charge transfer rate [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical degradation of R-6G relies on the mass and charge transfer; therefore, the surface area-to-volume (SA/V) ratio of the electrode material and the presence of active sites play a crucial role in the entire process. It is reported that array structures could provide a significant enhancement in many fields of study, such as catalysis [19][20][21][22][23], anti-reflection coatings [24,25], solar cells [26,27], optoelectronics [28], surface property modifications [29], and biomedical applications [30]. Recent research works demonstrated that improvement could originate from an increased SA/V ratio and surface energy content of the samples, the presence of active sites and defects, as well as the charge transfer rate [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate novel electrocatalysts, a smart way to enhance the efficiency of catalysis is to make array structures on electrode surfaces. Fabrication of arrays could be accomplished by various ways, including but not limited to focused ion beam (FIB) patterning, [143][144][145][146][147][148] lithography, [149][150][151] template-assisted method, [152][153][154] chemical etching [155][156][157][158][159] and so on. This section introduces the fundamentals of these techniques; the advantages and disadvantages will be compared as well.…”
Section: Increasing Aspect Ratio By Fabrication Of Array Structuresmentioning
confidence: 99%
“…It should be noted that metal ions (usually Ga + ) have much When a beam of ions is focused on the sample surface, a pre-set pattern could be introduced to guide the ion milling. [143][144][145][146][147][148] The focused beam scans along the designated paths and removes the surface particles due to ion bombardment, 161,162 thus leaving the desired pattern at the end of operation (Figure 2.19). On the other hand, FIB-induced CVD requires the participation of specially made organometallic precursors, which are to be installed on the instrument.…”
Section: Fib Patterningmentioning
confidence: 99%